Cytological Evaluation of Thyroid and its Correlation with Thyroid Function Test and Anti-Thyroid Peroxidase in a Patient of Hashimoto’s Thyroiditis - Das, Manish Kumar; Basnet, Meenakshi (Journal of Nobel Medical College, 2019)
Background: A thyroid swelling is an enlargement of thyroid glands causes by iodine deficiency, ageing, autoimmune disease and benign or malignant tumors. Autoimmune thyroiditis is the second most common thyroid lesion diagnosed after goiter.Materials and Methods: To find out the distribution of thyroid gland swelling in patients visiting otorhinolaryngology department of Nobel medical college and correlate serum thyroid function test and anti-thyroid peroxidase level with fine needle aspiration cytology reports.Results: The mean age of patient with thyroid gland lesions was 40.47 ± 13.05 years. Out of 87 patients studied, the highest number of patients (37, 42.5%) was diagnosed with colloid goiter followed by autoimmune thyroiditis (29, 33.3%). The mean age of patients with autoimmune thyroiditis was found to be 38.66 ± 12.31 years. The sensitivity and specificity of anti-thyroid peroxidase antibodies for diagnosing autoimmune thyroiditis was 89.7% and 94.8% respectively.Conclusion: Autoimmune thyroiditis has statistical correlation with serum anti-thyroid peroxidase antibodies and it can be effectively used as an alternative tool in diagnosing autoimmune thyroiditis with acceptable diagnostic accuracy.